Navigating Intra-National Culture Shock: A Case Study of Non-Javanese University Students in East Java, Indonesia - Sari, Nara (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This qualitative case study explores the experiences of culture shock among non-Javanese students studying at a university in Java, Indonesia. Despite staying within national borders, these students encountered significant cultural dissonance due to Indonesia’s rich ethnic and cultural diversity. Drawing from personal reflections and narratives of four students from various provinces, the study investigates how culture shock manifested, affected their academic engagement, and how individual backgrounds influenced their coping strategies. The findings reveal that language barriers, cultural hierarchy, and separation from family contribute to emotional and psychological stress, particularly during the initial stages of adaptation. However, shared living environments, age, academic level, and cultural proximity to Javanese norms played a critical role in either mitigating or amplifying the impact. This study highlights the importance of culturally responsive support in higher education institutions and suggests that culture shock, when positively navigated, can lead to personal growth and intercultural competence.